PENGARUH COVID-19 TERHADAP PEKERJA, BURUH, DAN USAHA MIKRO DI KABUPATEN TANGERANG - Apriani, Desy; Ade Martha, Wahyu Rama; Supriatna, Yayat (Jurnal Manajemen Retail Indonesia (JMARI), 2022)
Termination of employment, the impact on unemployment, difficulty finding work, the poor increase.Prediction of an increase in the number of poverty in Indonesia. The Corona Virus then appeared andgave so much influence in various sectors. One of the sectors that was affected and felt so much wasthe economic sector. This study aims to determine the effect of Covid-19 on Workers, Labor, andMicro Enterprises in Kab. Tangerang. This research uses descriptive qualitative method. In collectingdata using primary data, namely by using data collection techniques in-depth interviews, observation,and documentation. The Covid-19 pandemic not only has an impact on health, but also has an impacton the community's economy, especially informal workers who rely heavily on daily income. Based onthe results of the study, it can be concluded that the Pandemic can also have a disproportionateeconomic impact on certain segments of the population, which can exacerbate inequality that affectsmost groups of workers, such as: Workers who already have problems with health conditions, Youthwho are already facing unemployment and underemployment rates. higher unemployment, Olderworkers who may be at higher risk of serious health problems and likely to suffer from economicvulnerability, Women who are overrepresented in work who are on the front lines of dealing with thepandemic and who will bear a disproportionate burden of care responsibilities related to schoolclosures or care systems Unprotected workers, including self-employed, casual and performanceworkers who do not have access to paid or sick leave mechanisms and migrant workers who may notbe able to access the workplace m them in the destination country or return to their families.Uncertainty and difficulties in life make this vulnerable group need social safety nets, such as healthinsurance and social security. Through the provision of health insurance and social security, the livesof the most vulnerable people are protected, both in times of crisis and in times of crisis. With thissocial protection, vulnerable workers can live in healthy conditions and can still work to supportthemselves and their families in the future. Without health insurance and social security, the crisis dueto the Covid-19 pandemic will take away the hopes and lives of vulnerable groups